Statement of Peer Review - Nico Jehmlich (Biology and Life Sciences Forum)
In submitting conference proceedings to Biology and Life Sciences Forum, the volume editors of the proceedings certify to the publisher that all papers published in this volume have been subjected to peer review administered by the volume editors [...]